FEASIBILITY EVALUATION OF EARTHQUAKE RESISTANT REINFORCED CONCRETE DESIGN BASED ON GRAVITATION LOAD - Khairizal, Yuri
Earthquakes cause a large number of losses, whether in terms of material or casualties. The Aceh, Yogyakarta, Padang, Lombok and Palu earthquakes that occurred some time ago added to the history of the earthquake that caused huge losses in Indonesia. Non-engineered buildings or buildings that are not built technically have the possibility of greater damage to destruction if an earthquake occurs rather than engineered building. Some categories of simple buildings that often occur in damage include housing, shop houses and simple public facilities (education and health). There needs to be an increase in capacity of the construction industry, either by improving the quality of construction operators or making guidelines with minimum standards (easy to do), especially as a solution to reduce non-engineered building so the need for the design of earthquake resistant structures is fulfilled. Earthquake resistant structures design requires many analytical requirements that must be met, so that design procedures are difficult. For this reason, a simplier alternative procedure is needed so that the requirements for minimum guidelines or procedures can be fulfilled. This design method is generated from analysis of several structural models. Analysis is carried out based on the provisions of earthquake resistant structures according to the Indonesian National Standard (SNI). So using this design method will provide a good level of feasibility in meeting the requirements of earthquake resistant structures. The conditions of the analysis carried out in this method include linear and non-linear analysis, so that modeling and analysis of structures can be assessed well in these conditions. Based on comprehensive studies on several structural models, a modification pattern is needed so that the structural design meets the standards of analysis based on the provisions of earthquake resistant structures. This pattern of modification will be an alternative to the requirements of the earthquake resistant structure itself. The use of spreadsheets that are quite popular and easily accessible will be an option in designing this method. Simple structures that are constructed out without meeting technical or nonengineered building requirements are the focus of this study. Based on this, the structure model that is permitted to be used in this method will focus on cases of simple structures. Whereas to verify the condition of the condition, it will use several limitation limits. These limits are in the form of structures, earthquake conditions, building functions, structural systems and foundation conditions. For structures that are outside the boundary conditions, they are not accommodated by this design method. The general stages of this design method are divided into preliminary design stages and modified cross-section elements based on structural conditions. The preliminary design phase covers the preliminary design of the span structure, the force approach based on gravitation load and adjustments to special reinforcement requirements (special moment resisting frame system). While for the modification stage itself will adjust to the condition of the structure. After analyzing and evaluating of the structural modeling carried out in this study, the conditions that must be met were obtained. The results of the feasibility evaluation on several models conducted in this study indicate that this method is quite well used for structures up to 3 floors with 2-4 spans. Whereas for structures with a larger number of floors and spans, it is necessary to add structural rigidity by increasing the cross-sectional area of the structural column elements based on the results in the preliminary design stage of this design method.